2010
DOI: 10.1021/jp1002676
|View full text |Cite
|
Sign up to set email alerts
|

New Insights into Charge Flow Processes and Their Impact on the Activation of Ethene and Ethyne by Cu(I) and Ag(I) Sites in MFI

Abstract: This paper concerns the activation of ethene and ethyne molecules on two cationic sites (Cu(I) and Ag(I)) in ZSM-5 zeolite. QM/MM calculations were carried out to obtain geometric structure and vibrational frequencies. A novel analysis tool, NOCV (natural orbitals for chemical valence) supported by an ETS energy decomposition scheme, was applied to characterize charge flow between adsorbed molecules and the cationic site in ZSM-5 zeolite. The ETS-NOCV method allows for separating independent components of diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 85 publications
1
28
0
Order By: Relevance
“…As we have shown in this contribution and postulated previously for other molecules [28][29][30], in order to fully understand the nature of electron transfer between the active site and a ligand total differential density must be resolved into independent electron transfer channels since various symmetries and transfer directions may coexist, either corroborating or opposing activation. All the more for the NO ligand, which due to its specific open-shell electronic structure is a special case, and thus requires NOCV analysis with spin-resolution and careful selection of initial fragment density, prerequisite for defining proper deformation density.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…As we have shown in this contribution and postulated previously for other molecules [28][29][30], in order to fully understand the nature of electron transfer between the active site and a ligand total differential density must be resolved into independent electron transfer channels since various symmetries and transfer directions may coexist, either corroborating or opposing activation. All the more for the NO ligand, which due to its specific open-shell electronic structure is a special case, and thus requires NOCV analysis with spin-resolution and careful selection of initial fragment density, prerequisite for defining proper deformation density.…”
Section: Discussionmentioning
confidence: 73%
“…On the other hand, it was suggested, after analyzing atomic population changes upon ligand adsorption on a bare cation versus the cation embedded in a model environment that the unusual catalytic activity of transition-metal exchanged zeolites should be due to the activation of the transition-metal ion by the zeolite framework which functions as a specific ligand. Theoretical studies devoted to the interaction of small ligands with multiple bonds bound by zeolitic sites clearly indicated that the charge flow upon adsorption involves several transfer channels, strongly dependent on a zeolite framework type and a cation position [23,[26][27][28][29][30]. Populations within orbital resolution and devised selection schemes, frequently supported by topological analyses of electron density, were able to discriminate distinct electron transfers for a model metal-ligand bond [23,26,27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously studied distinct electron density transfer channels resulting from natural orbitals for chemical valence (NOCV) analysis (described in detail elsewhere) 8-10 performed for molecules coordinated to Cu(I) systems via a C-C multiple bond (benzene, ethene, or ethyne) [11][12][13] or an oxygen lone pair (formaldehyde). 13 NOCV orbitals diagonalize differential electron density (the difference between the electron density of a complex system and superimposed densities of non-interacting fragments, here a Cu(I) site and a ligand), and thus decompose global density flow accompanying ligand bonding by the site into independent density transfer channels.…”
Section: Introductionmentioning
confidence: 99%
“…In the present account we will describe the Mo-O bonding in the Mo 7 O 30 H 18 cluster using the recently developed extended transition state-natural orbitals for chemical valence (ETS-NOCV) approach [26] based on NOCV [27,28] and the ZieglerRauk bond-energy partitioning (ETS) [29]. This approach was successfully applied in characterizing various types of chemical bonds in inorganic and organic compounds, involving donor-acceptor, ionic and covalent bonds as well as relatively weak interactions (hydrogen bonds, agostic bonds) [26,[30][31][32]. The main advantage of the NOCVbased approach is that it allows one to separate the contributions to the deformation density originating from different components of the bond (r-, p-, d-), providing the corresponding charge-flow and energy estimates [26][27][28].…”
Section: Introductionmentioning
confidence: 99%